Percepção ambiental de alunos da educação de jovens e adultos - Cordeiro, Debora Rodrigues [UNIFESP] (2023)
This research aimed to plan, apply and evaluate a didactic intervention proposal in environmental education after characterizing the environmental practices of youth and adult education (EJA) students. Action research was used as a research methodology of an interventional nature at the state school Lydes Rachel Gutierrez in the city of Diadema - SP The data collection methods for each work context were: step 1: application of the instruments (environmental design, wheel of conversation and involving) to identify the environmental perception of the students, step 2: planning of the environmental intervention, step 3: application of the environmental intervention and step 4: evaluation of the results of the intervention. For the analysis of data referring to the detection of the environment in the investigative instruments, four categories of detection were protected (belonging, naturalist, adversary and socio-environmental criticism). For the analysis of the responses of the approaches, simple descriptive statistical analysis was used. The results of the investigative instruments pointed to the predominance of the perception of belonging in the design and naturalistic perception in traffic, reinforcing the need for more contextualized environmental practices. For the intervention in environmental education, we used the results of the investigative instruments for the awareness and involvement of the students in the development of the Articula Workshop aiming at the survey of the environmental problems and potentialities of the school community. With this work and its investigative and interventional instruments, it contributes to the formation of EJA students, enhancing the school as a learning space, transforms and critical exercise for the socio-environmental changes necessary in society.